Influence of NPK fertigation and foliar application on flower quality, media physico-chemical properties and foliar nutrient content in carnation (Dianthus caryophyllus) cv. Master - ARVINDER SINGH; NOMITA LAISHRAM; Y C GUPTA; B P SHARMA; B S DILTA; S K BHARDWAJ (The Indian Journal of Agricultural Sciences, 2015)
Sixteen different fertilizer treatments were accessed in a completely randomized block design for their effects on cut- flower grades, media physicochemical properties and foliar nutrient content in carnation (Dianthus caryophyllus L.) cv. Master plants grown under naturally ventilated greenhouse conditions at the Research Farm of Department of Floriculture and Landscaping, Dr Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, India during 2010 and 2011. Rooted cuttings were planted in a sterilized growing media comprising of soil: FYM: coco peat (2:1:1, v/v). Carnation cultivar Master plants fertilized with treatment comprising of 250 ppm N and K fertigation through urea and MOP + 250 ppm NPK (19:19:19) foliar spray once a week showed significant increase in quality parameters (i.e. percentage of A, B and C - grade flowers based on stem strength) in comparison to the recommended practices. Highest available NPK content in the media (371.03, 37.09, 276.87 kg/ ha) as well as in foliage (2.867, 0.364, 3.954 %) were also recorded with the same treatment.